Serum levels of gamma-glutamyltransferase predict outcome in heart failure with preserved ejection fraction - Dalos, Daniel (Sci Rep, 2019)
Previous studies suggested an association between heart failure (HF) and hepatic disorders. Liver function parameters have been shown to predict outcome in HF with reduced ejection fraction, but their impact in HF with preserved ejection fraction (HFpEF) has not yet been investigated. Between January 2011 and February 2017, 274 patients with confirmed HFpEF were enrolled (age 71.3 ± 8.4 years, 69.3% female) in a prospective registry. During a median follow-up of 21.5 ± 18.6 months, 97 patients (35.4%) reached the combined endpoint defined as hospitalization due to HF and/ or death from any cause. By multivariable cox regression, serum gamma-glutamyltransferase (GT) was independently associated with outcome (Hazard Ratio (HR) 1.002, p = 0.004) along with N-terminal pro brain natriuretic peptide (HR 2.213, p = 0.001) and hemoglobin (HR 0.840, p = 0.006). Kaplan-Meier analysis showed that patients with serum gamma-GT levels above a median of 36 U/L had significantly more events as compared to the remainder of the group (log-rank p = 0.012). By multivariable logistic regression, higher early mitral inflow velocity/ mitral peak velocity of late filling (Odds Ratio (OR) 2.173, p = 0.024), higher right atrial (RA) pressure (OR 1.139, p < 0.001) and larger RA diameter (OR 1.070, p = 0.001) were independently associated with serum gamma-GT > 36 U/L. Serum levels of gamma-GT are associated with both left and right-sided cardiac alterations and may serve as a simple tool for risk prediction in HFpEF, especially when further diagnostic modalities are not available.